GaAs n‐i‐p‐i solar cells with ion implanted selective contacts. Issue 4 (8th February 2013) - Royall, B.; Mazzucato, S.; Ketlhwaafetse, R. M.; Balkan, N.; Puustinen, J.; Guina, M.; Smith, A. J.
Abstract A GaAs n‐i‐p‐i doping solar cell with ion implanted selective contacts is grown, fabricated and investigated by spectral response and AM1.5G current‐voltage (I‐V) measurements. The device, whose active region consists of 4 layers of horizontal doping alternating n–p‐n‐p, is grown by molecular beam epitaxy (MBE). Electrical connection to layers in the middle of the device is achieved by creating vertical layers of p+ and n+ type doping by ion implantation of Mg and Si, respectively. The implants are 10 µm wide and spaced 100 µm apart. By carefully selecting the energies of the ions, the implants are kept away from the surface of the device, so that standard front/back contacts to be used. Spectral response measurements suggest that all layers of the device contribute to the photocurrent effectively. The device achieves Jsc = 12.9 mA/cm2 and Voc = 0.189 V for the AM1.5G 1 sun solar spectrum. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)